Assessment of the prevalence of Subclinical Mastitis through two on-farm tests in dual-purpose livestock system of Colombian Orinoquia - Arcesio Salamanca-Carreño; Mauricio Vélez-Terranova; Rita Tamasaukas; Raúl Jáuregui-Jiménez; Pere M. Parés-Casanova; José N. Arias-Landazábal (Journal of Applied Animal Research, 2023)
The assessment of the prevalence of Subclinical Mastitis (SCM) in dairy farms is essential to evaluate the health status of mammary gland. The aim of the study was to assess the prevalence of SCM in dual-purpose livestock systems in Arauca, Colombia, through the analysis the values found on-farm diagnostic California Mastitis Test (CMT) and Electric Conductivity (EC) test. Milk samples were taken from the individual mammary quarters of 481 cows. The cow level prevalence, per affected individual mammary quarters prevalence and the mammary quarter level prevalence were determined according to the values obtained for each test using two methods of analysis. An ANOVA was performed to determine the difference between prevalences. Cohen’s kappa coefficient was used for intertest agreement, and an analysis of sensitivity and specificity. The cow level prevalence was similar between the tests (CMT = 31.4%; EC = 29.7%). The quarter-level prevalence was lower with EC (11.4% vs 14.3%) (p < 0.05). The agreement test between CMT (0) and EC ranged between 0.20 and 0.25. Despite the low agreement found between the tests, they can be useful in determining the health status of the mammary gland in the dual-purpose livestock systems of the Colombian Orinoquia.